Penerapan Media Kurawa ( Kuis Interaktif Bahasa Jawa) Dalam Memahami Isi Teks Cerita Mahabaratha Bima Bungkus Kelas X MIPA 4 SMA Negeri 3 Pemalang Tahun Ajaran 2021/2022 - Riyandanti, Dian Lestari; Alfiah, Alfiah; Sulanjari, Bambang (Universitas PGRI Semarang, 2022)
This research was motivated by the lack of optimal learning of Javanese language at SMA Negeri 3 Pemalang because the selection of media that was less attractive for story-text-based learning made the enthusiasm of students in participating in learning decrease. Thus, the formulation of the problem taken is how the results of the application of the Kurawa media (Javanese interactive quiz) in understanding the content of the Mahabharata Bima Bungkus story text. The purpose of this research is to describe the results of the application of the Kurawa media (Javanese interactive quiz) in understanding the content of the Mahabharata Bima Bungkus story.This research is included in descriptive quantitative research because there is a calculation of statistical data needed to determine the relationship with the phenomenon under study so that the results of these calculations show the basic relationship between empirical observations and quantitative data. The source of this research data is the result of students' scores in learning to understand the content of the story text Mahabaratha Bima Bungkus, with research data in the form of data processing results using statistical formulas. The technique used in collecting data is non-probability sampling in the form of purposive sampling technique.Based on the data analysis, the following research results were obtained: 1) In terms of knowledge, there were 32 students who had met the KKM with an average score of 90.72. 2) In the skills aspect, there are 34 students who have met the KKM with an average score of 83.5.